A topic map based learning management system to facilitate meaningful grammar learning: the case of Japanese grammar learning - Wang, Jingyun; Wynn, Adam; Mendori, Takahiko; Hwang, Gwo-Jen (Smart learning environments, 2024)
This study investigates the effect of studying with topic maps provided by a self-developed language learning support system on (a) learning perception, (b) learning achievement and (c) variation in learning attitude and motivation, from the perspective of prior learning attitude, motivation and learning style. An analysis was conducted on the learning data of 90 participants for examining pre-test and post-test scores, learning perception, learning style indicators, attitude and motivation rankings before and after the study of target Japanese grammar content with the support of the system. The findings suggest that learners with high attitude/motivation perceived greater development of the habit of “learning from the comparison of related knowledge” and felt more satisfied with the learning situation in the system environment. Furthermore, the learners' attitude towards Japanese grammar learning and their motivation toward Japanese language learning were significantly stronger after the learning activity. It is also observed that (a) learner attitude towards Japanese grammar after studying with the system only had a positive correlation to prior attitudes; and (b) learner motivation towards Japanese language after studying with the system correlated highly with prior motivation and perception of development of the habit of “learning from the comparison of related knowledge.” Finally, from a learning style perspective, the analysis result suggests that “Global learners” expressed a stronger feeling about the usefulness of the comparison function of the system and their increment in motivation after using the system was higher than for “Sequential learners.” Moreover, between learning style indicators in the Sequential/Global dimension and level of learner expertise in the reported mental load scale, a significant interaction effect was found.